Estudo de marcadores químicos de guaraná (Paullinia cupana) por CLAE - Stark, Gisele (2007)
Guaraná, Paullinia cupana var. sorbilis (Mart.) Ducke, is one of the most important natural products of the Amazon basin and very appreciated abroad. The Indians of low Amazon due to its stimulating, fortifying and anti-diarrhea properties consume it and today guarana is also cultivated in other states of Brazil. Its seeds, powdered or as syrup, are used in many products (beverages). The main chemical constituents of guarana are methylxanthines (caffeine, theofiline, theobromine) and also phenolic compounds (catechins). Due to the increasing interest for guarana, adulteration based on synthetic caffeine addition (low cost) has been more often found. This adulteration cannot be detected by the main quality control methods based on the quantification of caffeine. This work describes the development of an analytical method developed by reversed phase high performance liquid chromatography to acquire chromatographic profiles (fingerprints) of guarana to quality control and assess adulteration of guarana based on the analysis of its multicomponents. The fingerprints were very reproductible, relative to five chemical markers (caffeine, catechin, epicatechin, theofiline and theobromine). The method was also able to quantify caffeine in the samples. Twenty samples from three different states in Brazil (Amazonas, Bahia and Mato Grosso) were analysed and a common fingerprint, independent from its origin, was obtained. The caffeine content of the samples could assess the geographical origin. The certification of origin of a natural product is one of the most important added values. The antioxidant power of powdered guarana seeds obtained in two different ways (toasted or sun dried) were also evaluated and compared to other plant species consumed worldwide as beverages and recognized for their antioxidant power (green tea, black tea, coffee, mate and barley). The sample of toasted guarana had a significant antioxidant power, inferior only to green tea, whereas the sun dried sample have much less activity. This indicates the great potential of guarana and the importance of the drying process of the seeds to keep its nutraceutical properties. Key-words: Chromatographic profile, antioxidant activity, HPLC, quality control, phenolic, methylxanthines.